Highly active, stable and self-antimicrobial enzyme catalysts prepared by biomimetic mineralization of copper hydroxysulfate. Issue 40 (4th October 2016) - Li, Zhixian; Ding, Yi; Li, Shaomin; Jiang, Yanbin; Liu, Zheng; Ge, Jun
Abstract : To address the activity–stability contradiction, enzymes encapsulated in spindle-like copper hydroxysulfate nanocrystals by a nature-inspired, facile and general approach exhibit both high activity and high stability, and additional self-antimicrobial properties at the same time. Abstract : A nature-inspired approach to encapsulate enzymes in spindle-like copper hydroxysulfate nanocrystals was developed by a biomimetic mineralization process. Several types of enzymes including glucose oxidase (GOx), horseradish peroxidase (HRP), Candida antarctica lipase B (CALB) and cytochrome c (Cyt c) were successfully encapsulated in copper hydroxysulfate nanocrystals quickly (within 1 hour) with maintained or even greatly enhanced catalytic efficiencies ( k cat / K M of Cyt c showed a 143-fold increase) and high stabilities, demonstrating the feasibility of utilizing copper hydroxysulfate nanocrystals as a novel type of nanocarrier for enzyme immobilization. In addition, by this approach, for the first time, we showed that an immobilized enzyme can be endowed with self-antibacterial activity by an inorganic component. This self-antibacterial performance together with the improved catalytic efficiencies and stabilities can greatly benefit the enzymatic catalysis in aqueous media and promote the future development of novel biosensors.